Meningkatkan Perkembangan Sosial Emosional Dengan Permainan Tradisional Bakiak Pada Anak Usia 5-6 Tahun - Cicih, Cicih; Haryono, Mimpira; Asnawati, Asnawati (Early Childhood Research and Practice, 2025)
The purpose of this research is to find out whether traditional clog games can improve social emotional development in children aged 5-6 years at PAUD Gemilang, Kepahiang Regency. This research is a type of Classroom Action Research (PTK) which is focused on classroom situations, or commonly known as classroom action research, the procedures used are cyclical. The main subjects in this study were children aged 5-6 years totalling 15 people. This research uses the Jhon Elliot model where each cycle consists of four activities, namely planning, implementation, observation, and reflection which are carried out through two cycles. Data collection techniques using observation and documentation methods. Data analysis was carried out descriptively qualitative-quantitative. The results of children's cognitive development through the application of montessori methods in group B at Gemilang PAUD Unit, Kepahiang Regency, in cycle I was 74.16% (BSH) and in cycle II showed an increase of 89% (BSB). It is concluded that traditional clog games can improve social emotional development in children aged 5-6 years at PAUD Gemilang Kepahiang Regency. Evidently in cycle II there was a significant increase, the percentage result was 89% (BSB).